PRECAUTIONARY MEASURES FOR EARLY DETECTION AND TREATMENT OF BRUCELLOSIS DISEASE. (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article examines how important the spread of brucellosis among people is today and measures to prevent its spread. Epidemiological features of the disease, spreading factors and diagnostic methods were analyzed in the study. The focus is on the implementation of effective preventive measures against the disease, including vaccination programs, compliance with sanitary and hygiene rules, and raising awareness of the population. The article describes strategies for the prevention of whooping cough.